Fifty major cities of the Bible: from Dan to Beersheba - Laughlin, John C. H. (Routledge key guides, 2006)
From the ruins of the ancient seaside city of Acco, to the small but archaeologically important town of Yokneam, "Fifty Major Cities of the Bible" provides readers with a comprehensive guide to the ancient cities that played a vital role in the world from which the Bible originated. Not only covering renowned cities such as Jerusalem and Jericho, the book also includes lesser known towns like Aroer, Beth-Zur and Gibeah, which have all provided their own valuable contributions to the way in which we now understand the biblical world. It is a fascinating, easy-to-follow text, with key features including: the biblical context of each city or town; a summary of its known archaeological history; non-biblical references to the site; photographs and illustrations; and a concise bibliography for further reading. Also provided is a handy reference map to the major archaeological sites in Israel, as well as chronological tables for easy reference. Concise, informative and high accessible, "Fifty Major Cities of the Bible" is a superb overview of the cities and towns that made up the Biblical world, and an essential resource for students and enthusiasts.